An experimental study on the optimization of the production and efficiency of tunable Helmholtz absorbers for the modal control of small rooms. Issue 2 (June 2019) - Thomazelli, Rodolfo; Bertoli, Stelamaris
Helmholtz absorbers are a common solution for controlling the low-frequency modes found in small rooms. These devices only perform in a narrow spectrum range with the tuning depending on each room's geometrical configurations. Consequently, their development still operates on a case-by-case basis. A possible alternative to optimize the production of these acoustic solutions is the development of a tunable Helmholtz absorber capable of changing its geometrical configurations according to each room's acoustic needs. The present work shares the results of tests performed on varied samples of different configurations of absorbers. The samples were chosen aiming the control of the three first modes of each direction in rooms with volume ranging from 20 to 60 m 3 . The research revealed that the use of a single tunable absorber has the potential to produce sound absorption coefficients higher than 0.8 in almost the entirety of the frequency spectrum considered.